Risk and outcomes of complications during and after MitraClip implantation: Experience in 828 patients from the German TRAnscatheter mitral valve interventions (TRAMI) registry. Issue 4 (12th February 2015) - Eggebrecht, Holger; Schelle, Sibylle; Puls, Miriam; Plicht, Björn; von Bardeleben, Ralph Stephan; Butter, Christian; May, Andreas E.; Lubos, Edith; Boekstegers, Peter; Ouarrak, Taoufik; Senges, Jochen; Schmermund, Axel
<x xml:space="preserve">Abstract</x> Aims To analyze risk and outcomes of complications during and after MitraClip implantation using multicenter data from the prospective German Transcatheter Mitral Valve Interventions (TRAMI) registry. Methods and Results Data of 828 patients (mean age: 76.0 [71–81] years, 327 (40%) females) undergoing MitraClip implantation in Germany between 2010 and 2013 were analyzed. Most patients (85%) underwent elective procedures with on average implantation of 1.4 ± 0.6 clips. Emergent cardiac surgery was not required; a single patient died intraoperatively. During the in‐hospital period, complications occurred in 215 (25.9%) patients, of which 106 (12.8%) were considered major. Major bleeding complications were among the most frequent major complications (7.4%), while rates of pericardial tamponade (1.9%) and clip‐specific complications (embolization: 0%, partial clip detachment: 1.9%) were low. In‐hospital death, stroke or myocardial infarction (MACCE) occurred in 2.2, 0.9, and 0% patients, respectively. Patients with complications appeared to be older and more critically ill pre‐interventionally; in‐hospital mortality was significantly higher as compared to those without procedural complications. Conclusions MitraClip implantation appears to be a safe treatment option with low rates of MACCE and clip‐specific complications. Nevertheless, MitraClip therapy is not without complications. Careful patient selection and improvements in preventing peri‐procedural bleeding have the potential of reducing post‐procedural complications and improving outcomes. © 2015 Wiley Periodicals, Inc.